Local Culture and Gender Differences in Educational Participation: A Study in Kwala Besar Village, Langkat Regency, North Sumatra, Indonesia - Sukmana, Oman; Damanik, Fritz Hotman Syahmahita; Martins, Alibere; Muhammad, Gibran (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
Local culture has an impact on gender participation in education. This research examines how local cultural values affect gender gaps in education participation in Kwala Besar Village, Langkat Regency, North Sumatra. Information was gathered through observations and interviews with different informants (parents, students, teachers and community members). The results show a strong gender gap in attendance at school, with more girls than boys going to school at each level. This disparity reflects community values whereby local boys are encouraged to drop out of school early compared to girls encouraged to attend higher education. It is an unequal system that does not allow for balanced social development; boys are not participating effectively in future economic opportunities as a result of a lack of education, and girls are not placed in significant roles that allow them to contribute to the development of the community. The study demonstrates the strong impact of local cultural values upon the opportunities available to the younger generation, and will be of interest to researchers, policymakers, educators, and development practitioners looking to plan culturally sensitive interventions to advance gender equity in education and community development.